The Efficacy of Transactional Analysis Training on Mother’s Parenting Stress and Parental Acceptance of Aggressive Gifted Children - Nejatifar, Sara; Aghaziarati, Ali; Abedi, Ahmad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study was conducted to investigate the effectiveness transactional analysis training on parenting stress of mothers and parental acceptance of aggressive gifted children. Methods: The present study was quasi-experimental with pre-test, post-test, and a control group. The statistical population of this study included aggressive gifted boys aged 8-12 years in Tehran in 2021. Thirty children were selected by purposive non-random sampling and their mothers assigned into experimental (n =15) and control (n =15) groups. The experimental group received transactional analysis intervention in eight 120- minute sessions. The data were collected by the Parenting Stress (Abidin 1990) and the parental acceptance- rejection questionnaire (Rohnner 2007). Data were analyzed using repeated measures variance. Results: The results showed that the transactional analysis had an effect on reducing maternal parenting stress and increasing parental acceptance of aggressive gifted children. Also, the results of analysis of covariance showed that the effect of interaction behavior analysis training on parenting stress (F= 10.33) and parental acceptance (F=34.50) was significant (P<0.05). Conclusion: According to the findings of this study, it can be stated that transactional analysis training by recognizing existential values and improving interpersonal communication leads to reducing parenting stress and increasing parental acceptance of gifted aggressive children.